Iowa Birdline update, November 30, 1992 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1992)
Email of Iowa Birdline updates for November 30, 1992. The highlights for the update include sightings of two Short-eared Owls and two Long-eared Owls, a very late Common Yellowthroat and a late American Golden-Plover. Also included are handwritten notes with sightings of a Northern Goshawk that returned to the northside Marion neighborhood for the seventh straight day and two first year Thayer's Gulls below the Red Rock Dam. Epson - sheet feed/flatbed